Natural Fiber Improvement by Laccase; Optimization, Characterization and Application in Medium Density Fiberboard. Issue 3 (4th May 2017) - Nasir, Mohammed; Hashim, Rokiah; Sulaiman, Othman; Gupta, Arun; Khan, Tanveer Ahmed; Jawaid, Mohammad; Asim, Mohd
ABSTRACT: Crystallinity of cellulosic fiber directly affects the physical and chemical behavior of the individual fiber and ultimately the product made from. In a controlled condition, if the natural fiber is exposed to enzymatic hydrolysis, its crystallinity improves without affecting the cellulose component of the fiber. In this work, four basic factors for enzymatic reaction, i.e., temperature, time, pH, and enzyme amount, were optimized using response surface methodology (RSM). The response was taken as the fiber crystallinity index, measured by X-ray diffraction method. The optimum treated fiber was further analyzed for the field emission scanning electron microscopy (FE-SEM), thermogravimetric analysis (TGA) and results were compared with untreated fiber. Medium density fiberboards (MDF) were manufactured from optimum treated fiber and its tensile properties and water resistance properties were compared with MDF made from untreated fiber. The observation revealed a maximum of up to 14% increment in fiber crystallinity index (CrI) as compared to untreated fiber. The MDF prepared from optimum treated fiber exhibits improved tensile property and lower water absorption property as compared to MDF prepared from untreated fibers.